Dosis crecientes de bayfolan suelo azul en el rebrote de Morus nigra “morera” y su influencia en el rendimiento del forraje en Zungarococha, Perú – 2022 - Perez Gallardo, Wendi (2023)
The research work was carried out at the National Amazon University of Peru in the Faculty of Agronomy in a livestock project on the Zungarococha farm called "INCREASING DOSES OF BAYFOLAN SOIL AZUL IN THE RESPROUP OF Morus nigra “MORERA” AND ITS INFLUENCE ON FORAGE YIELD IN ZUNGAROCOCHA, PERU – 2022". The evaluations were carried out 45 days after sowing in plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2. With a design of complete blocks at random (D.B.C.A), with five treatments and four repetitions, the treatments under study were: T0 (0 kilos of Bayfolan/ha), T1 (50 kilos of Bayfolan/ha), T2 (100 kilos of Bayfolan nitrogen/ha ) and T3 (150 kilos of Bayfolan/ha), obtaining the following results: With the T3 treatment (150 kilos of Bayfolan/ha) it was possible to increase the averages of green matter (kg/m2), dry matter (kg/m2) , yield of stems (kg/m2), yield of leaves (kg/m2), yield of kg/plot (3.6 m2) and yield kg/ha. In this sense, it was shown that at least one of the doses of Bayfolan blue soil in regrowth influences the yield of whole plant green matter, leaves, stems, and dry matter per square meter, plot, and hectare of Morus nigra “Mulberry” forage. According to what was found in this work, a higher dose of Bayfolan/ha results in improvements for the forage yield of the pasture.